Mobile and more productive? Firm-level evidence on the productivity effects of mobile internet use - Irene Bertschek; Thomas Niebel (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2015)
Mobile internet access allows for flexibility with respect to working time and working place. We analyse whether employees' use of mobile internet access improves firms' labour productivity. Our data set contains 2143 German firms and refers to the year 2014, when high-speed mobile internet was still at a relatively early stage of diffusion within firms. The econometric analysis shows that firms' labour productivity significantly increases with the share of employees with mobile internet access. Our instrumental variables approach reveals that mobile internet use does cause higher labour productivity.
urn:nbn:de:bsz:180-madoc-405209
Keywords: D22; L20; O33; 330; Mobile Internet; Labour Productivity; Firm-Level Data